Market-sensing capability, knowledge creation and innovation: The moderating role of entrepreneurial-orientation - Abdallah Mohammad Alshanty; Okechukwu Lawrence Emeagwali (Journal of Innovation & Knowledge (JIK), 2019)
This article examines the nexus between market-sensing capability, knowledge creation, strategic entrepreneurial-orientation and innovation in small and medium sized enterprises (SME). Data was garnered from (n=255) SMEs operating in Jordan and a covariance-based structural equation modelling (CB-SEM) was applied to analyze the data. SEM result illustrates a positive effect of market-sensing capability on (1) knowledge creation, and (2) firm innovation. Knowledge creation process has positive effect on (3) firm innovation. Knowledge creation process (4) mediated the link between market-sensing capability and firm innovation. Strategic entrepreneurial-orientation moderates the link between (5) knowledge creation and firm innovation, such that the positive relationship became weaker when strategic entrepreneurial-orientation is high. Theoretically and empirically this study has contributed to the existing inconsistent findings, and also offer useful managerial insights.
Keywords: 650; Innovations; Knowledge management; Market-sensing; Strategic entrepreneurial-orientation